Polarographic determination of ascorbic acid in roselle juice samples - Omar, Rosila (Universiti Sains Malaysia, 2015)
Ascorbic acid which is also known as vitamin C cannot be synthesised in human body. Hence, it is important to get the vitamin C from other source such as roseile juice. The recommended daily intake of vitamin C is 60 mg/day. Polarography technique has been used to determine the concentration of vitamin C in the roseile juice samples. The parameters for polarography technique for ascorbic acid determination are as follows: start potential: -0.0499 V, end potential: 0.1299 V, deposition potential: 0.55 V, deposition time: 15 s, equilibrium time: 10 s, voltage step: 0.005951 V, voltage step time: 0.6 s, sweep rate: 0.0099 V/s, pulse amplitude: 0.05 V, and pulse time: 0.04 s. The electrolytes used were 10 ml deionised water and 1 ml acetate buffer with pH of 4.64. The peak potential of ascorbic acid was found at 0.063 V. From five commercial roseile juice samples, three of them give a positive result on the ascorbic acid content. In the analysis of raw samples, it was found that the leaves have higher levels of vitamin C compared to calyces. As the conclusion, polarography technique was a successful applied for the determination of ascorbic acid in commercial roseile juice samples and raw samples such as roseile calyces and leaves.